'A Hymn', Hymnody and Anne Brontë's Religious Poetry. (2nd January 2022) - Butterworth, Robert
Abstract : Anne Brontë's 'A Hymn' was written at a time when hymns were 'of the moment' and many women were engaged in hymnody. It shares with Anne's other religious poems a vision of God as mighty, powerful, loving, merciful and actively interventionist, and a vision of humanity as feeble, inadequate, inconstant and inconsistent. It is distinguished by its exploration of two versions of the universe: one informed by God its Creator and the other its Godless alternative. 'A Hymn' has many traditional stylistic features of hymns and on one level belongs to a familiar class of hymn, the hymn of doubt; but it is also radical in facing head-on an atheistic vision emerging in the nineteenth century.